Eucalyptus and Corymbia Species for Pulpwood, Mulchwood, Energywood, Windbreaks, and/or Phytoremediation - Donald L. Rockwood; Gary F. Peter (EDIS)
In Florida, Eucalyptus species grow faster than our native tree species. E. grandis (EG), E. grandis x E. urophylla (EH), E. benthamii (EB), and E. amplifolia (EA), in particular, are fast-growing trees that, when planted on suitable sites and managed properly, produce commercial products such as mulchwood, pulpwood, energywood, and bioproducts. Eucalyptus can also phytoremediate, i.e., remediate environmental problems (Table 1). Eucalyptus species are not invasive, having been planted commercially in Florida since the 1960s without spreading from managed plantations. EG and EA, along with Corymbia torelliana (CT), also may be used as windbreaks for citrus and vegetables. This circular describes potential applications and presents planting guidelines for these species.